Parasites and their vectors : a special focus on Southeast Asia - Vythilingam, Indra (Springer Vienna Imprint: Springer, 2013)
Southeast Asia is a region where a myriad of infections are endemic. It is a hotspot region for parasitic diseases. Currently, information on parasitic infections and vectors found in Southeast Asia is sporadic and there has been no attempt to extensively collate and integrate these data. Gaps in our knowledge, which include disease patterns, transmission dynamics and vectors still exist. This book highlights parasitic diseases that are peculiar to Southeast Asia, pinpoints similarities and differences between disease patterns in the respective member countries and provide information on new emerging parasitic diseases in this region. Critically, this book will heighten understanding of parasitic diseases and their vectors in this diverse region and this knowledge will be significant for future regional research efforts in this field.